2008
DOI: 10.1029/2007gl032303
|View full text |Cite
|
Sign up to set email alerts
|

Tundra lake changes from 1978 to 2001 on the Tuktoyaktuk Peninsula, western Canadian Arctic

Abstract: Landsat scenes spanning 1978–2001 were used to classify thermokarst lake area and determine changes in lake coverage on the Tuktoyaktuk Peninsula in northwestern Canada. Changes in total lake area between scenes were substantial, spanning a 14% increase and 11% decrease, mostly owing to changes in the area of lakes >1.3 km2 in area. Increases in total lake area occurred primarily between 1978–1992, and decreases between 1992–2001. Differences in total lake area between scenes from different years depend strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(169 citation statements)
references
References 23 publications
2
162
4
1
Order By: Relevance
“…The role of storage deficit from C. D. ARP ET AL. / 393 the preceding season is an important process for ACP watersheds suggested by Bowling et al (2003) and observed in Landsat timeseries analysis of lake area extent for this region (Jorgenson et al, 2005;Jones et al, 2009a) and other ACP landscapes (Plug et al, 2008;Arp et al, 2011 ). The summer of 2009 was considered very wet and relatively cool and cloudy; the lower storage deficit from 2008 conditions combined with relatively large snowpack likely resulted in the much higher water yield.…”
Section: Hydrologic Behavior Water Yield and Flow Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of storage deficit from C. D. ARP ET AL. / 393 the preceding season is an important process for ACP watersheds suggested by Bowling et al (2003) and observed in Landsat timeseries analysis of lake area extent for this region (Jorgenson et al, 2005;Jones et al, 2009a) and other ACP landscapes (Plug et al, 2008;Arp et al, 2011 ). The summer of 2009 was considered very wet and relatively cool and cloudy; the lower storage deficit from 2008 conditions combined with relatively large snowpack likely resulted in the much higher water yield.…”
Section: Hydrologic Behavior Water Yield and Flow Regimesmentioning
confidence: 99%
“…In ACP watersheds, the extreme seasonality in wetland extent is a well documented phenomena that controls watershed water balance and runoff (Roulet and Woo, 1988;Bowling et al, 2003). Interannual variability in ACP lake-area extent is also strongly tied to precipitation (Plug et al, 2008;Jones et al, 2009a) and evaporation (Roulet and Woo, 1988;Rovansek et al, 1996;Kane et al, 2008) regimes. Additionally, thermokarst lakes, which form in ice-rich permafrost and are the dominant lake type on the ACP and other Arctic landscapes, expand by shoreline erosion with detectable increases in surface area for individual lakes and regionally (Smith et al, 2005) at decadal time scales.…”
Section: Linking Watershed Structure With Hydrologic Functionmentioning
confidence: 99%
“…The majority of available studies had a rather limited geographic coverage (<10,000 km 2 , [16,32,33]), or described relatively small regions within larger territories [29]. The high resolution studies, down to 0.1 ha lake size, dealt with even smaller territories (700 km 2 in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been proposed to obtain the dilution factor (e.g., Mook, 1980;Pearson and Hanshaw, 1970;Tamers, 1975;Vogel, 1970Vogel, , 1967Vogel and Ehhalt, 1963). In this study, a δ 13 C-mixing model modified by Clark and Fritz (1997) from the Pearson model (Pearson and Hanshaw, 1970) was applied to correct the 14 C dilution by carbonate dissolution. This model is based on variations in 13 C abundance, which differs significantly between the soil-derived DIC and carbonate minerals in the aquifer and is thus a good tracer of DIC evolution in groundwaters.…”
Section: The 14 C Age Modelmentioning
confidence: 99%
“…At high latitudes, permafrost distribution may affect lake density in addition to surface flow (Anderson et al, 2013). In areas of continuous permafrost, subpermafrost groundwater is often isolated from the surface, and there are unique mechanisms in thermokarst lake dynamics such as lateral expansion and breaching (Jones et al, 2011;Plug et al, 2008). Permafrost is now warming and thawing in many regions of the world (e.g., Anderson et al, 2013), and connections between permafrost degradation and local hydrologic changes have been established (e.g., O'Donnell et al, 2012;Yoshikawa and Hinzman, 2003).…”
Section: Introductionmentioning
confidence: 99%